Analysis the Implementation of the Webbed Type Integrative Thematic Learning Approach in 2013 Curriculum Context in Elementary School 1 Sukarame Bayongbong Garut - Neni Nadiroti Muslihah; Risma Nuriyanti; Siti Ropah Purnamasari; Ejen Jenal Mutaqin (Universitas Sebelas Maret, 2021)
This study aims to describe the related planning, implementation, assessment, and obstacles the webbed type integrative thematic learning approach. This research uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. Data analysis used the Miles and Huberman model, namely data reduction, data display and conclusions. The results showed that (1) the webbed type integrating thematic learning planning that was carried out was in accordance with the Indonesian Minister of Education and Culture Regulation No. 22/2016 on Basic and Secondary Education Process Standards. (2) the implementation of webbed type integrative thematic learning the teacher has carried out the three stages, namely preliminary activities, core activities and closing activities. (3) assessment of the webbed type of integrated thematic learning in the teacher learning process using observation sheets and assessment reflections, while the assessment at the end of teacher learning uses written tests and oral tests. (4) the obstacles experienced by the teacher, namely the determination of time allocation, the delivery of material in class I that is not in accordance with the situation and condition of the students, the teacher must be able to understand the methods and strategies